Material Weakness in Internal Controls and Stock Price Crash Risk. (January 2020) - Lobo, Gerald; Wang, Chong; Yu, Xiaoou; Zhao, Yuping
We investigate the association between material weakness in internal controls (MW) disclosed under Section 302 of the Sarbanes–Oxley Act of 2002 (SOX) and future stock price crash risk. We argue that relative to firms with effective internal controls, firms with MW have lower financial reporting precision. The lower reporting precision (a) increases divergence of investor opinion with regard to firm valuation and (b) facilitates managers' withholding of negative information, which increases the information asymmetry between managers and outside investors. We hypothesize that both these effects increase the probability of a future stock price crash. We find empirical evidence consistent with our prediction. In additional analyses, we document that the positive association between MW and crash risk is primarily driven by company level rather than by account-specific weaknesses, increases with the number of material weaknesses, and intensifies during the financial crisis. In addition, we find that both the existence and the disclosure of MW incrementally affect crash risk, and that MW facilitates managers' withholding of bad news. Finally, we fail to find consistent evidence of a significant relation between MW disclosed under Section 404 of SOX and crash risk.